Pengembangan Sistem Informasi Manajemen Bimbingan Belajar Berbasis Web dengan Pendekatan Data Mining untuk Analisis Performa Siswa Menggunakan Framework Laravel - Atika Fauziyyah; Tomy Nanda Putra; Dori Gusti Alex Candra; M. Agung Vafky Ideal; Budi Permana Putra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This research is motivated by the need for a system capable of managing tutoring institution data effectively while accurately analyzing student performance. The main problem at Brigade Nusantara is that data management is still conducted manually and there is no data-based analysis available to support decision-making processes. This study aims to develop a web-based Tutoring Management Information System using the Laravel framework with a data mining approach to analyze student performance. The system development method includes the stages of requirements analysis, system design, implementation, and testing. The data mining approach is utilized to process students’ historical data in order to generate information in the form of performance patterns, learning progress levels, and recommendations for academic improvement. The results of the study indicate that the developed system is capable of improving data management efficiency, facilitating the monitoring of student progress, and supporting accurate and data-driven decision making. Therefore, this system is expected to enhance the overall quality of tutoring services and assist administrators in developing more effective and targeted learning strategies.